A Socio-Cultural Analysis of Users’ Intentions to Use Facemask in the Post Covid-19 Era in Nigeria - Bolarinwa, Mojisola; Adeosun, Paul (European Scientific Journal, ESJ, 2024)
This paper investigates individuals’ intention to use facemasks in the post-COVID-19 era using the extended unified theory of acceptance and use of technology. During the COVID-19 pandemic, enforcement, rather than individual choice, drove facemask usage. In the post-COVID-19 era, the effects of facilitating condition, social influence, price value, performance expectancy, effort expectancy, hedonic motivation, experience and habit on the intention to use the facemask were investigated using the regressions analyses. A total of 417 respondents took part in the selection from government organisations, including higher institutions and public offices in South-West Nigeria and the Federal Capital Territory (Abuja). The result shows that facilitating conditions and hedonic motivation positively influenced the intention to use the facemask, while price value, experience and habit have negative impacts. Findings from this study suggest that facemask manufacturers and distributors must suitably design their products to suit the value perception of the user and beliefs that trigger social status and hedonic motivations in conjunction with the primary health benefits of the facemasks. It is recommended that further improvement of the facemask technology, such that it can convert traditional facemasks into smart technology with increasing emphasis on fashion and style, while adhering to safety measures be promoted by policymakers and manufacturers. While facemask manufacturers must see that the quality of their products meets up to ASTM (or relevant) standards, for which user-friendly, durable, microbe-resistant, yet biodegradable materials have been used, policymakers must organise regular sensitization programs on the importance of mask usage, and as well promote continuous development of improved technologies for nosemask designs.